Socioeconomic status, frailty, and subjective well-being : a moderated mediation analysis in elderly Chinese - Yang, Fang (2019)
The study examined the mechanisms underlying the link between socioeconomic status and subjective well-being and explored the role of social activities using a representative sample of older adults (N = 2773) in Shanghai, China. Results show that frailty mediated the relationship between socioeconomic status and subjective well-being, and social activities moderated the model, such that the mediation effect of frailty was significant only when social activities were lower. Moreover, the moderated mediation model was significant only for women, not for men. Findings highlight the importance of addressing frailty of older adults and promoting social activities (especially for elderly women) in future interventions.